Conventional Video-gastroscopes for the Recognition of Early Gastric Cancers - İNCE, ALİ TÜZÜN; Ince, ALİ TÜZÜN; SENATES, Ebubekir; BAHADIR, Ozgur; COSGUN, Suleyman; GUNES, Pembegul; YILDIZ, Eray; OVUNC, Ayse Oya Kurdas (My University, 2011)
Background/Aims: To determine the role of conventional video-gastroscopes for detection of early gastric cancers (EGC).